Genotoxic and immunotoxic effects of cellulose nanocrystals in vitro. (24th September 2014) - Catalán, Julia; Ilves, Marit; Järventaus, Hilkka; Hannukainen, Kati‐Susanna; Kontturi, Eero; Vanhala, Esa; Alenius, Harri; Savolainen, Kai M; Norppa, Hannu
<x xml:space="preserve">Abstract</x> Nanocellulosics are among the most promising innovations for a wide‐variety of applications in materials science. Although nanocellulose is presently produced only on a small scale, its possible toxic effects should be investigated at this early stage. The aim of the present study was to examine the potential genotoxicity and immunotoxicity of two celluloses in vitro ‐ cellulose nanocrystals (CNC; mean fibril length 135 nm, mean width 7.3 nm) and a commercially available microcrystalline (non‐nanoscale) cellulose (MCC; particle size ∼50 µm). Both celluloses showed 55% cytotoxicity at approximately 100 µg/ml after 4‐h, 24‐h, and 48‐h treatment of human bronchial epithelial BEAS 2B cells, as determined by luminometric detection of ATP and cell count (dead cells identified by propidium iodide). Neither of the materials was able to induce micronuclei (MN) in binucleate or mononucleate BEAS 2B cells after a 48‐h treatment (2.5–100 µg/ml). In human monocyte‐derived macrophages, MCC induced a release (measured by enzyme‐linked immunosorbent assay; ELISA) of the pro‐inflammatory cytokines tumor necrosis factor α (TNF‐α) and (after lipopolysaccharide‐priming) interleukin 1β (IL‐1β) after a 6‐h exposure to a dose of 300 µg/ml, but CNC (30–300 µg/ml) did not. In conclusion, our results show that nanosized CNC is neither genotoxic nor immunotoxic under the conditions tested, whereas non‐nanosized MCC is able to induce an inflammatory response. More studies are needed, especially in vivo, to further assess if CNC and other nanocelluloses induce secondary genotoxic effects mediated by inflammation. Environ. Mol. Mutagen. 56:171–182, 2015. © 2014 Wiley Periodicals, Inc.